PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS VIII SMP NEGERI 1 BANUHAMPU - Ironika, Sonia (Jurnal Edukasi dan Penelitian Matematika, 2024)
–  Along with their progress in mathematics education, students must develop the ability to solve mathematical problems of increasing complexity. Research conducted at SMP Negeri 1 Banuhampu shows that this competency is still lacking. The purpose of the study was to determine whether the Problem Based Learning (PBL) method in teaching this competency is effective or not. The participants in this study were eighth grade students from SMP Negeri 1 Banuhampu. A simple random selection strategy was used to select the sample classes (class VIII.9 and VIII.8). For the control group, we used a non-equivalent posttest only design. The results support the acceptance of the alternative hypothesis (H1) if the P-value is smaller than the significance threshold (?). The Problem-Based Learning paradigm is proven to improve problem-solving skills through empirical evidence. Keywords – Problem Based Learning, Mathematical Problem Solving Ability, Direct Learning